Adapting speaking activities in Tieng Anh 11 to improve students' participation at Dan Phuong Upper-secondary school - Phùng, Thị Hoa Mơ (University of Languages and International Studies, 2017)
Chapter 1: Literature review: An overview of students’ participation; Adaptation is a necessary task in less. Chapter 2: The study: Research setting; Research design; Participants; Data collection instruments. Chapter 3: Data analysis and findings: Results from before-experiment-observations; Results from students’ questionaire; Results from teacher interview; Results from the end of experiment observations; Students’ participation in experimental and control group in three lessons at the end of the intervention. Comparison of students’particpation before and at the end of the experiment.